Phát biểu khai mạc kỳ họp thứ 10, Quốc hội khóa XIII của Chủ tịch Quốc hội Nguyễn Sinh Hùng - Nguyễn Sinh Hùng (2015)
Phát biểu khai mạc kỳ họp thứ 10, Quốc hội khóa XIII của Chủ tịch Quốc hội Nguyễn Sinh Hùng (ngày 20/10/2015)